SYMPOSIUM SUMMARY: LOOKING TOWARD 2000 - William M. Healy (Wildlife Society Bulletin)
Abstract: National Wild Turkey Symposia have been an important means of communication among biologists. Proceedings of the 6 Symposia contain over 160 papers, more than any other source of technical literature. The Symposia provide a record of turkey (Meleagris gallopavo) restoration and the development of concepts about habitat requirements. Research in the next decade should focus on developing a unified theory of habitat use and a better understanding of population dynamics. Trap‐and‐transfer programs will continue to be important for population restoration, and they will become important for managing existing populations. Recent theoretical advances are being applied to restoration and management programs. The number of turkey hunters has grown dramatically; it is estimated that turkey hunters spent about $567 million in 1989. The popularity of turkey hunting and innovations in hunting equipment will challenge hunter education programs. State agencies will emphasize safe, quality hunting rather than maximum sustained harvest. The greatest challenge will be communicating management goals to a largely urban population. Managing turkey populations and hunters will be easy in comparison.